2010
DOI: 10.1177/1753193410362848
|View full text |Cite
|
Sign up to set email alerts
|

Re-visiting Luck’s classification: a histological analysis of Dupuytren’s disease

Abstract: Luck (1959) described a histological staging system for Dupuytren's disease, classifying the disease into three stages. Previous biochemical and immunochemical studies have detailed the decrease in type III/I collagen ratio with disease progression. Herovici (1963) described a histological stain that produced a differential red/purple and blue colour for type I and III collagen respectively. We stained 15 specimens of Dupuytren's disease and quantified the different collagen types in each using computer analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 14 publications
1
32
0
3
Order By: Relevance
“…In this regard, our results demonstrated that DDC had significantly more collagen content than NPF and NFF as determined by picrosirius and Masson's trichrome staining, and that collagen fibers were highly organized and oriented only in DDC tissues, with an increase in the ratio of type III to type I collagen as compared to controls. The concentration of collagen fibers oriented in the same direction is one of the main factors related to the pathogenicity of this disease, in which contracture cords are predominantly composed of an oriented fibrous structure [32] mainly consisting of collagen fibers [12]. Our histological analysis also revealed that the amount of collagen fibers in NPF almost duplicated the amount found in control NFF, with the ratio of type III to type I collagen being similar in DDC and NPF.…”
Section: Discussionsupporting
confidence: 64%
“…In this regard, our results demonstrated that DDC had significantly more collagen content than NPF and NFF as determined by picrosirius and Masson's trichrome staining, and that collagen fibers were highly organized and oriented only in DDC tissues, with an increase in the ratio of type III to type I collagen as compared to controls. The concentration of collagen fibers oriented in the same direction is one of the main factors related to the pathogenicity of this disease, in which contracture cords are predominantly composed of an oriented fibrous structure [32] mainly consisting of collagen fibers [12]. Our histological analysis also revealed that the amount of collagen fibers in NPF almost duplicated the amount found in control NFF, with the ratio of type III to type I collagen being similar in DDC and NPF.…”
Section: Discussionsupporting
confidence: 64%
“…6 This technique has been used to subjectively analyze keloid scars and Duputyren contractures. 7,8 The Herovici stain has been used to quantify the amount of types I and III collagen within mature burn scars, providing an objective analysis. 9 Despite anecdotal reports that ablative lasers improve scars, to our knowledge, no formal investigation has quantified improvement or possible underlying mechanisms.…”
mentioning
confidence: 99%
“…Lam et al 11 added an analysis of collagen type to Luck's classification of Dupuytren disease. Fifteen surgical specimens were evaluated using collagen-specific stains to identify the relative percentages of type I versus type III collagen.…”
Section: Basic Researchmentioning
confidence: 99%